2014
DOI: 10.1371/journal.pgen.1004547
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Identification of Single Nucleotide Polymorphisms Associated with Beta-lactam Resistance within Pneumococcal Mosaic Genes

Abstract: Traditional genetic association studies are very difficult in bacteria, as the generally limited recombination leads to large linked haplotype blocks, confounding the identification of causative variants. Beta-lactam antibiotic resistance in Streptococcus pneumoniae arises readily as the bacteria can quickly incorporate DNA fragments encompassing variants that make the transformed strains resistant. However, the causative mutations themselves are embedded within larger recombined blocks, and previous studies h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
239
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(254 citation statements)
references
References 59 publications
11
239
1
Order By: Relevance
“…In S. pneumoniae, beta-lactam resistance has been shown to associate with a number of variants outside the direct target of beta-lactams (the peptidoglycan biosynthesis pathway) (20). It seems plausible that some of these variants may play a role in determining duration of carriage.…”
Section: Discussionmentioning
confidence: 99%
“…In S. pneumoniae, beta-lactam resistance has been shown to associate with a number of variants outside the direct target of beta-lactams (the peptidoglycan biosynthesis pathway) (20). It seems plausible that some of these variants may play a role in determining duration of carriage.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these assays are solely PCR based (40)(41)(42)(43), although sequencing approaches and microarrays have also been used (45,46). Several recent studies have also compared phenotypic drug susceptibility testing results with predictions based on whole-genome sequencing (WGS) data for a variety of bacterial pathogens (47), including S. pneumoniae (48,49). Our CDC-based laboratory has developed a promising WGS-based "typing pipeline" for rapid and automated predictions of pneumococcal serotypes, MICs, genotypes, and additional features (50).…”
Section: Detection Of Antibiotic Resistancementioning
confidence: 99%
“…Another recent genomewide association study identified a set of 301 single nucleotide polymorphisms, from which 73 caused amino acid alterations in cell-wall synthesis genes [20].…”
Section: Beta-lactam Resistancementioning
confidence: 99%